The role of intersecting identities in career development and progression in the core disciplines of the South African mining industry - Mahobe, Patience Ntsoaki (University of the Witwatersrand, Johannesburg, 2024)
The study sought to contribute to scholarship in the South African mining industry related to career development and progression in the core disciplines. Using qualitative research methods and applying intersectionality as a theoretical framework, the study examined whether, and how social identity plays a role on career development and progression in the core disciplines (mining & technical services, metallurgy, and engineering) of the South African mining industry. The study further examined whether there has been a change in the experiences of the different social identity groups related to career development and progression in the nearly thirty years since the promulgation of various pieces of legislation in South Africa in the mid- to late 1990s across industries and the mining industry in the early 2000s to transform the demographic profile across various occupational levels. The study lastly determined whether historical and current organisational, industry and societal systemic issues and dynamics impact career development and progression in these core disciplines. Thematic analysis was used to systematically identify and organise the data from the narratives of the participants provided through semi-structured interviews. This study confirms that intersectional identities have an impact on the career development and progression in core disciplines in the South African mining industry. The application of intersectionality as a theoretical framework brought to the fore different career development and progression experiences, challenges, and outcomes for the different social identity groups. Some progress in changing the demographic of the industry was noted, although progress is seen as being slow, particularly at executive level, with historical systemic issues related to entrenched ways of working and a leadership style that is not people-centric being the most difficult to change. The outcomes of the study and recommendations challenge the industry to think differently about transforming their cultures and ways of working, to create a focus on macro-level organisational systems and structures that continue to produce and reproduce unequal outcomes whilst also creating awareness and dealing with micro-level individual behaviour
A research report Submitted in fulfillment of the requirements for a Master of Arts in the field of Diversity Studies, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Intersectionality; social identity; career development; career progression; mining industry; SDG-7: Affordable and clean energy